A Structural and Functional Model for the Tris‐Histidine Motif in Cysteine Dioxygenase. Issue 40 (24th June 2019) - Anandababu, Karunanithi; Ramasubramanian, Ramamoorthy; Wadepohl, Hubert; Comba, Peter; Johnee Britto, Neethinathan; Jaccob, Madhavan; Mayilmurugan, Ramasamy
Abstract: The iron(II) complexes [Fe(L)(MeCN)3 ](SO3 CF3 )2 (L are two derivatives of tris(2‐pyridyl)‐based ligands) have been synthesized as models for cysteine dioxygenase (CDO). The molecular structure of one of the complexes exhibits octahedral coordination geometry and the Fe−Npy bond lengths [1.953(4)–1.972(4) Å] are similar to those in the Cys‐bound Fe II ‐CDO; Fe−NHis : 1.893–2.199 Å. The iron(II) centers of the model complexes exhibit relatively high Fe III/II redox potentials ( E 1/2 =0.988–1.380 V vs. ferrocene/ferrocenium electrode, Fc/Fc + ), within the range for O2 activation and typical for the corresponding nonheme iron enzymes. The reaction of in situ generated [Fe(L)(MeCN)(SPh)] + with excess O2 in acetonitrile (MeCN) yields selectively the doubly oxygenated phenylsulfinic acid product. Isotopic labeling studies using 18 O2 confirm the incorporation of both oxygen atoms of O2 into the product. Kinetic and preliminary DFT studies reveal the involvement of an Fe III peroxido intermediate with a rhombic S = 1 / 2 Fe III center (687–696 nm; g ≈2.46–2.48, 2.13–2.15, 1.92–1.94), similar to the spectroscopic signature of the low‐spin Cys‐bound Fe III CDO (650 nm, g ≈2.47, 2.29, 1.90). The proposed Fe III peroxido intermediates have been trapped, and the O−O stretching frequencies are in the expected range (approximately 920 and 820 cm −1 for the alkyl‐ and hydroperoxido species, respectively). The model complexes have a structure similar to that of the enzyme and structural aspects as well as the reactivity are discussed. Abstract : The iron(II) complexes of a tris(2‐pyridyl)‐based ligand are presented as accurate structural models for cysteine dioxygenase (CDO). With O2 they selectively convert sulfur‐based substrates into doubly oxygenated products via a Fe III ‐peroxido reaction intermediate.